High-dose chemotherapy with BEAC regimen and autologous bone marrow transplantation for intermediate grade and immunoblastic lymphoma: Durable complete remissions, but a high rate of regimen-related toxicity - Van Besien, K.; Tabocoff, J.; Rodriguez, M.; Andersson, B.; Mehra, R.; Przepiorka, D.; Dimopoulos, M.; Giralt, S.; Suki, S.; Khouri, I.; Spitzer, G.; Jagannath, S.; et al. (Bone Marrow Transplantation, 1995)
Forty-eight adult patients with recurrent or refractory intermediate grade or immunoblastic lymphoma received high-dose carmustine (BCNU), etoposide, Ara C and cyclophosphamide (BEAC), followed by autologous bone marrow transplantation (BMT). Median follow-up is 906 days (range 613-2067 days). The complete remission rate was 42% and 22% had a partial response. Actuarial failure-free survival is 30% ± 6.6%. Twenty one patients relapsed or progressed. Only one relapse occurred > 1 year after autologous BMT. Adverse prognostic factors for failure-free survival include high LDH at the time of autologous BMT, chemotherapy-refractory disease and multiple prior relapses. Patients with chemotherapy responsive first salvage (those achieving first CR only with salvage chemotherapy and those with first relapse, responding to salvage chemotherapy) had a failure-free survival of 52% ± 10% vs 12% ± 6% for those with more advanced disease. Of 13 patients who had no adverse factors, only two relapsed. Treatment-related mortality occurred in 23%, including infection (n = 4), cardiac toxicity (n = 4), pulmonary toxicity (n = 2) and hemorrhage (n = 1). Pulmonary toxicity was more common among patients who had received prior radiation-therapy to the chest. BEAC chemotherapy with autologous BMT is an effective but relatively toxic regimen for patients with relapsed or refractory lymphomas. The combination of chemotherapy-responsive disease after failure of one chemotherapy regimen and normal LDH identifies patients with a favorable prognosis. Alternative cytotoxic regimens require evaluation, with the goal of reducing treatment related mortality. More effective cytoreductive therapy is required for patient with poor prognostic features.
Keywords: BEAC; Lymphoma